Differences in Baseline Characteristics and Outcomes at One-and Two-Year Follow-up of Cancer Survivors Accrued via Self-Referral versus Cancer Registry in the FRESH START Diet and Exercise Trial - Snyder, Denise Clutter (2008)
Participant accrual to research studies is a challenge, and oftentimes advertisements are used to supplement cases ascertained through clinic caseloads and cancer registries. It is unknown however, if cases ascertained through these two sources differ. In this study, we compare self-referred (n=209) versus cancer registry-ascertained participants (n=334) enrolled in FRESH START, a randomized controlled trial promoting a healthy diet and increased exercise among breast and prostate cancer survivors. The two groups were compared on baseline characteristics, adherence, attrition, and outcomes by study arm. Compared to participants enrolled from registries, self-referrals were significantly younger (54.1±10.4 vs. 58.7±10.7 years), more likely to have later-staged disease and to have received chemotherapy (40% vs. 19%), and more likely to report “fighting spirit” coping styles (50% vs. 30%), lower quality-of-life (88.2+15.1 vs. 92.0+12.9), fewer co-morbid conditions (1.87±1.60 vs. 2.24±1.78), and lower consumption of 5 or more daily servings of fruits and vegetables (35% vs. 45%)(p-values <.05). While no differences in behavior change were observed between self-referred and registry-ascertained cases assigned to the tailored intervention arm, this was not the case within the attention control arm. Among those who received the attention control intervention of standardized materials in the public domain, self-referred versus registry-ascertained participants demonstrated significantly greater increases in exercise at 1-year follow-up, and significantly greater increases in fruit and vegetable consumption at both 1- and 2-year follow-up (p-values <.05). Several differences exist between self-referred versus registry-ascertained participants, including motivation to respond to standardized educational materials which appears significantly greater in self-referred populations.